2002
DOI: 10.1017/s0012162201002936
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment in infancy: impact on neurodevelopmental and neurobiological processes

Abstract: IntroductionThis review draws together current understanding of the impact of visual impairment (VI) on early neurodevelopmental and neurobiological processes. The impact is recognized as being substantial. Two major problems make it difficult to draw conclusions from much of the literature on this subject. The first is the heterogeneity of samples of children with VI in terms of additional impairments that introduce multiple confounding variables: in Western societies the prevalence of additional impairments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(137 citation statements)
references
References 97 publications
2
132
0
Order By: Relevance
“…If this is true, then the likelihood of autism among congenitally blind children would be increased by other factors that also limit such experience. Such factors might be as diverse as neurological dysfunction on the one hand, or adverse rearing conditions on the other (e.g., Keeler, 1958;Mukaddes et al, 2007;Sonksen & Dale, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…If this is true, then the likelihood of autism among congenitally blind children would be increased by other factors that also limit such experience. Such factors might be as diverse as neurological dysfunction on the one hand, or adverse rearing conditions on the other (e.g., Keeler, 1958;Mukaddes et al, 2007;Sonksen & Dale, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The risks that have been identified so far include any visual disorder, male gender, multiple brain lesions, the nought to two year age period and profound visual impairment (lack of 'form' vision). Some preliminary evidence also suggests that profound visual impairment under 10-16 months, even if 'form' vision emerges later, and adversity in the psychosocial and familial environment may also be risk factors (see reviews by Sonksen and Dale, 2002;Dale, 2005).…”
Section: Researching Early Developmental Processes and Risksmentioning
confidence: 99%
“…Our recent research has demonstrated that children with dpotentially simpleT congenital disorders of the peripheral visual system (dpotentially simpleT CDPVS) are the most appropriate subgroup for establishing developmental norms [5,7]. We have also shown that development is likely to proceed at different rates in infants who have dformT vision compared with those without.…”
Section: Development Of the New Monitoring Protocolmentioning
confidence: 99%
“…Through a series of research studies spanning 25 years, our team has demonstrated that impaired vision can impose far-reaching and complex constraints on early development including motor, cognitive, language and social development [3][4][5]. Constraints on any target skill are often cumulative, acting directly upon it and also on one or more of the skills that underpin its acquisition [4].…”
Section: Lessons Learned About Infants With Severe Visual Impairmentmentioning
confidence: 99%
See 1 more Smart Citation